1996
DOI: 10.1046/j.1365-2249.1996.d01-867.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to membranes of endothelial cells and fibroblasts in scleroderma

Abstract: SUMMARYAnti-endothelial and other cell membrane-reactive antibodies in scleroderma were characterized by immunoblotting sera with membrane and cytosol preparations of human umbilical vein endothelial cells (HUVEC), dermal fibroblasts and a T cell lymphoma HUT78. Antibodies reactive with HUVEC membranes were found in 17 of 20 patients with scleroderma (33 bands) in contrast to only two of 20 controls (two bands; P<0 . 01) and three of 11 patients with myocardial infarction (four bands). Eleven of the 20 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 23 publications
0
49
0
2
Order By: Relevance
“…Several studies found that the prevalence of AECA in systemic sclerosis varied from 20% to 80%, according to whether the disease was in its limited or diffuse form: 23% in primary Raynaud's phenomenon, 44% in limited scleroderma, and 84% in diffuse scleroderma (6,47,48). However, AECA in systemic sclerosis are not EC specific.…”
Section: Disease Association and Prevalence Of Aecamentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies found that the prevalence of AECA in systemic sclerosis varied from 20% to 80%, according to whether the disease was in its limited or diffuse form: 23% in primary Raynaud's phenomenon, 44% in limited scleroderma, and 84% in diffuse scleroderma (6,47,48). However, AECA in systemic sclerosis are not EC specific.…”
Section: Disease Association and Prevalence Of Aecamentioning
confidence: 99%
“…However, AECA in systemic sclerosis are not EC specific. Namely, AECA characterized by immunoblotting with membrane preparation of HUVEC exhibited a cross-reactivity with other cell types such as fibroblasts and a T cell lymphoma line (6). In addition, antibodies against a 19-kd protein, apparently associated with the CREST (calcinosis, Raynaud's phenomenon, esophageal dysmotility, sclerodactyly, telangiectasias) syndrome, were shown to possess anticentromere activity (6).…”
Section: Disease Association and Prevalence Of Aecamentioning
confidence: 99%
See 1 more Smart Citation
“…In sera from SSc patients with lung involvement, the proteomic approach allowed the identification of new targets for anti-endothelial cell antibodies (AECA), which further support the role of EC damage as central event in the pathogenesis of the disease [30][31][32]. In particular, Negi et al [32] observed a significantly higher incidence of PAH in AECA positive patients.…”
Section: Serum Interface For Proteomic Analysis Of Soluble Biomarkersmentioning
confidence: 99%
“…A recent microarray analysis of SSc dermal fibroblasts found that SSc-related autoantigens, including centromeric protein B, fibrillarin, a largest subunit of RNAP II, and topo I, were up-regulated in SSc dermal fibroblasts obtained from affected skin compared with those from unaffected skin, suggesting a possible association between overexpression of SSc-specific autoantigens in the affected fibroblasts and the specific autoantibody responses (6). In contrast, autoantibodies reactive with dermal fibroblasts have been reported in sera from SSc patients (7)(8)(9)(10), but fibroblast-specific autoantigens have not been identified to date.…”
Section: S Ystemic Sclerosis (Ssc)mentioning
confidence: 99%